Functional Genetic Diversity and Culturability of Petroleum-Degrading Bacteria Isolated From Oil-Contaminated Soils - Sun, Ji-Quan; Xu, Lian; Liu, Xue-Ying; Zhao, Gui-Fang; Cai, Hua; Nie, Yong; Wu, Xiao-Lei (Frontiers in Microbiology, 2018)
In this study, we compared the culturability of aerobic bacteria isolated from long-term oil-contaminated soils via enrichment and direct-plating methods; bacteria were cultured at 30°C or ambient temperatures. Two soil samples were collected from two sites in the Shengli oilfield located in Dongying, China. One sample (S0) was close to the outlet of an oil-production water treatment plant, and the other sample (S1) was located 500 meters downstream of the outlet. In total, 595 bacterial isolates belonging to 56 genera were isolated, distributed in Actinobacteria, Firmicutes, Bacterioidetes, and Proteobacteria. It was interesting that Actinobacteria and Firmicutes were not detected from the 16S rRNA gene clone library. The results suggested the activation of rare species during culture. Using the enrichment method, 239 isolates (31 genera) and 96 (22 genera) isolates were obtained at ambient temperatures and 30°C, respectively, from S0 soil. Using the direct-plating method, 97 isolates (15 genera) and 163 isolates (20 genera) were obtained at ambient temperatures and 30°C, respectively, from two soils. Of the 595 isolates, 244 isolates (41.7% of total isolates) could degrade n-hexadecane. A greater number of alkane-degraders was isolated at ambient temperatures using the enrichment method, suggesting that this method could significantly improve bacterial culturability. Interestingly, the proportion of alkane degrading isolates was lower in the isolates obtained using enrichment method than that obtained using direct-plating methods. Considering the greater species diversity of isolates obtained via the enrichment method, this technique could be used to increase the diversity of the microbial consortia. Furthermore, phenol hydroxylase genes (pheN), medium-chain alkane monooxygenases genes (alkB and CYP153A), and long-chain alkane monooxygenase gene (almA) were detected in 60 isolates (11 genotypes), 91 isolates (27 genotypes) and 93 isolates (24 genotypes), and 34 isolates (14 genotypes), respectively. This study could provide new insights into microbial resources from oil fields or other environments, and this information will be beneficial for bioremediation of petroleum contamination and for other industrial applications.